Colonialism, Institutional Change, and Shifts in Global Labour Relations - Zwart, Pim; Hofmeester, Karin (Amsterdam University Press, 2018)
This book offers a view of shifts in labour relations in various parts of the world over a breathtaking span, from 1500 to 2000, with a particular emphasis on colonial institutions.